Wormseed (Teloxys aristata (L.) Moq., Amaranthaceae Juss.) – new alien genus and species for Belarusian flora - Dzhus, Maxim A. (Experimental Biology and Biotechnology, 2017)
New alien species for the Belarusian flora – Teloxys aristata (L.) Moq. (Amaranthaceae) is briefly characterized in the article. Teloxys aristata – is an annual species of Central Asian origin, occurring sporadically as alien weed in Europe, East Asia and North America and continuously increasing in distribution. This genus and species are reported for the first time from Belarus. Revision of herbarium specimens revealed that it was first collected in 2001 as casual immigrant on the tracks near the railway station Lida (Grodno District, NW Belarus). The new locality corrects the total range of this species in Europe and completes taxonomical list of Amaranthaceae family in Belarusian flora.
Keywords: Amaranthaceae; Teloxys aristata; Chenopodium aristatum; Dysphania aristata; new locality; distribution; Belarus